Architects negligence on building defects in Malaysia / Raihana Abdul Rahman and Stephanie Sherron Abbie - Abdul Rahman, Raihana; Abbie, Stephanie Sherron (2007)
Negligence is the most well-known and certainly the most important of all torts. Negligence, particularly by a group of professionals, may occur everyday and at anytime in our daily life. Hence, an attempt is made to examine the liability of the architects for their negligence on building defects and the awarded damages that would be imposed on them. This project paper is limited to literature review, research, analysis and suggestion based on the objectives and scope of study. This research is conducted to analyze and evaluate the liability of architects towards the end user in ascertaining the concept of duty of care in applying the neighbourhood principles, foreseeability test and the reasonable man's test with reference to relevant statutes and cases. This research in addition will examine whether statutory provisions governing architects is desirable in Malaysia relating to the liability of the architects for their negligence act and to create awareness to the public on the area of professional liability of architects in Malaysia. We have concluded that the existence of duty of care by applying the neighborhood principle is essential in determining whether a person can be made liable in negligence. There is an urgent need to codify the law relating to architects negligence in the statute since there is no express provision that regulate the conduct of the architects therein.